A high-stability PC / PBT alloy material and preparation method thereof
By introducing transesterification inhibitors, carboxylated carbon nanotubes and hydrophobic agents into PC/PBT alloy materials, the problem of insufficient stability of the material in humid and thermal photoaging environment is solved, and the effect of high stability and excellent mechanical properties is achieved, which is suitable for the application of automotive parts.
Patent Information
- Application Number
- CN202211504201.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-28
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2042-11-28
AI Technical Summary
The existing PC/PBT alloy materials have low thermal deformation temperatures under high loads, poor notch impact performance, and insufficient stability in humid and thermal photoaging environments, making it difficult to meet the application requirements of automotive parts.
In the components of PC/PBT alloy materials, the combined effect of these components improves the comprehensive stability and mechanical properties of the material.
It realizes high stability and excellent mechanical properties of PC/PBT alloy materials in humid and thermal photoaging environment, and can maintain good appearance performance stability without spraying paint. It is suitable for the preparation of automotive parts with high humidity and thermal photoaging resistance.
Smart Images

Figure BDA0003966207870000081 
Figure BDA0003966207870000082 
Figure BDA0003966207870000091
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer alloy materials, and in particular to a high-stability PC / PBT alloy material and a preparation method thereof. Background Art
[0002] Polycarbonate (PC) / polybutylene terephthalate (PBT) alloy material is a polymer alloy material prepared by blending PC and PBT. Among them, the PBT component is a crystalline polyester material with advantages such as good solvent resistance and good processing fluidity, but it has a low heat deformation temperature under high load and poor notch impact performance; while the PC component is an amorphous polymer with good dimensional stability, good toughness, and excellent rigidity in a wide temperature range, but it has a high melting temperature that leads to processing difficulties, large residual stress in molded products, and poor chemical resistance, especially when encountering solvents such as aromatic compounds, esters and ketones. At the same time, in the conventional PC and PBT melt blending modification process, since both have ester structures, ester exchange reactions are prone to occur during the melt blending process, and it is impossible to improve the shortcomings of a single component and achieve the effect of combining the advantages of the two, which seriously limits the application of PC / PBT alloy materials in various fields, especially in the automotive field with high requirements for stability and mechanical properties.
[0003] In order to overcome the above problems, it is usually necessary to add an ester exchange inhibitor to the preparation components of PC / PBT alloy materials to control the ester exchange reaction of PC and PBT during the melt processing, and at the same time, by introducing toughening modifiers or compatibilizers (such as ethylene-octene copolymers, core-shell structured methyl methacrylate-butadiene-styrene, silicone rubber, etc.), the relevant mechanical properties requirements of PC / PBT alloy materials used in automotive parts such as bumpers, door handles, and luggage racks are met. However, the above parts still need to be protected by spraying paint on the surface in actual application, and currently many automobile OEMs have proposed the demand for non-painted PC / PBT alloy parts. Summary of the invention
[0004] Based on the defects of the prior art, the purpose of the present invention is to provide a highly stable PC / PBT alloy material. In addition to introducing an ester exchange inhibitor, carbon nanotubes containing a specific content of carboxyl groups and a specific type of hydrophobic agent are introduced into the material components to work together, so that the obtained PC / PBT alloy material has high comprehensive stability, especially in the face of wet, hot and light aging environment, it has excellent mechanical properties and appearance performance stability without painting.
[0005] In order to achieve the above object, the technical solution adopted by the present invention is:
[0006] A PC / PBT alloy material comprises the following components in parts by weight:
[0007] 55-75 parts of PC resin, 25-35 parts of PBT resin, 3-7 parts of toughening agent, 0.5-2 parts of carboxylated carbon nanotubes, 1-3 parts of hydrophobic agent and 0.2-0.5 parts of transesterification inhibitor;
[0008] The ratio of the melt flow rate of the PC resin at 300°C to the melt flow rate of the PBT resin at 250°C is (1-3):1; the hydrophobic agent is glycidyl methacrylate grafted polyethylene, and the grafting rate is 0.5%-1.5%.
[0009] In the prior art, the performance of PC / PBT alloy materials that are of concern are mainly basic mechanical properties and stability in different environments. However, at the current product testing stage, the environment used to test its stability is basically a hot environment, which is used to examine the thermal oxidation aging performance of the product, and not much attention is paid to some other common environmental factors (humidity, light). As the automobile parts move with the car, they may not only be subject to external thermal oxidation aging, but may also be affected by high humidity and long light environments, which weakens the stability of the PC / PBT alloy components they contain. The inventors have found that most of the existing products that are simply modified with ester exchange inhibitors and toughening agents cannot meet the performance stability requirements in a long-term wet heat and light aging environment without painting.
[0010] Based on the above situation, the inventor introduced specific carboxylation carbon nanotubes and hydrophobic agents into the component system of the existing modified PC / PBT alloy material, wherein the carbon nanotubes containing a specific content of carboxyl groups can be connected with the terminal hydroxyl groups of the PBT resin in the material on the one hand, reducing the probability of the ester exchange reaction between it and the PC resin in the component to a certain extent, and on the other hand, the carbon nanotubes have a heterogeneous nucleation effect in the component, effectively improving the crystallinity of the PBT resin, and further improving the product's resistance to wet heat and light aging. Glycidyl methacrylate grafted polyethylene does not act as a compatibilizer in the product component. In the PC and PBT resin system, due to the large polarity difference between polyethylene and the two resins, polyethylene has a low melting point and high fluidity. Therefore, glycidyl methacrylate grafted polypropylene actually migrates to the surface of the product after the product preparation process, which has a good protective effect on the product, especially the role of protecting the external water; in addition, glycidyl methacrylate with a specific grafting content will react with the carboxylation carbon nanotubes, and cooperate with the carboxylation carbon nanotubes to jointly shield the light (especially ultraviolet rays) radiated to the surface of the product, which plays a role in improving the product's light aging resistance. At the same time, the inventors have found through experiments that the grafting rate of glycidyl methacrylate grafted onto polypropylene cannot be too high or too low: if the grafting rate is too low, polyethylene will be completely free from the component system during the product preparation process, which may cause internal stratification of the product and directly affect the mechanical properties of the product; and if the grafting rate is too high, glycidyl methacrylate may decompose into small molecules during the subsequent product preparation process, ultimately leading to weakening of the product performance.
[0011] At the same time, the inventors found that for the key resin matrices PC resin and PBT resin, if the melt flow rates of the two resins are greatly different, it is easy to form a skin-core structure. Based on the common types of PC resin and PBT resin currently available on the market, the outer layer of the skin-core structure is mostly PBT resin, but since the PBT resin's resistance to wet heat and light aging is generally poor, the stability of the resulting product cannot meet the requirements of automotive parts in wet heat and light aging environments. Therefore, it is necessary to limit the melt flow rates of the two resins within a certain ratio range so that the viscosity difference between the two is relatively small, and the two resins are evenly distributed in the product without forming a skin-core structure.
[0012] Preferably, the PC / PBT alloy material also includes 0.2 to 2 parts of processing aids.
[0013] More preferably, the processing aid is at least one of an antioxidant and an ultraviolet absorber.
[0014] More preferably, the processing aid is a mixture of an antioxidant and an ultraviolet absorber, the weight portion of the antioxidant is 0.4 to 1 part, and the weight portion of the ultraviolet absorber is 0.1 to 1 part.
[0015] More preferably, the antioxidant is at least one of a hindered phenol antioxidant and a phosphite antioxidant; and the ultraviolet absorber is a benzotriazole ultraviolet absorber.
[0016] Based on actual conditions, those skilled in the art may further add suitable processing aids, especially ultraviolet absorbers, to the product components. Since the components of the product described in the present invention include glycidyl methacrylate grafted polyethylene and carboxylated carbon nanotubes, which can effectively shield the light radiation received by the surface of the product, the ultraviolet absorber introduced into the component can be effectively protected from rapid degradation by ultraviolet rays, thereby making the product have higher light aging resistance.
[0017] Preferably, the carboxyl content of the carboxylated carbon nanotubes is 1-2 wt %.
[0018] The preparation method of the carboxylated carbon nanotubes is as follows:
[0019] The carbon nanotubes are placed in a mixed acid (concentrated sulfuric acid and nitric acid are mixed in a volume ratio of 3:1), ultrasonically treated for 2 to 5 hours, and then refluxed at 80°C for 1 to 3 hours; then diluted with deionized water and left for 24 hours to precipitate until the supernatant is yellow; the supernatant is removed, and the lower dispersion is filtered with a polyvinylidene fluoride microfiltration membrane with a pore size of 0.2 μm and repeatedly washed with deionized water until the dispersion becomes neutral, and then dried at 100°C to obtain carboxylated carbon nanotubes. The carboxyl content of the carboxylated carbon nanotubes can be calculated by acid-base titration.
[0020] Among the components of the PC / PBT alloy material of the present invention, the carboxyl groups on the carbon nanotubes are mainly connected to the PBT resin. If the content is low, the degree of inhibition of the transesterification reaction between the PBT resin and the PC resin is weakened, and it cannot fully react with the hydrophobic agent. However, if the content is high, the structure of the carbon nanotubes is severely damaged, reducing the light shielding effect of the carbon nanotubes, thereby weakening their protective effect on the PC / PBT alloy material. Based on the inventor's further preference, the carboxyl carbon nanotubes have the best effect in the product components when the carboxyl content is 1 to 2 wt%.
[0021] Preferably, the PC resin is tested for melt flow rate at 300° C. and 1.2 kg load according to ISO 1133-2012, and the melt flow rate of the PC resin is 8 to 15 g / 10 min.
[0022] Preferably, the melt flow rate of the PBT resin is tested at 250° C. and 1.2 kg load according to ISO 1133-2012, and the melt flow rate of the PBT resin is 5 to 8 g / 10 min.
[0023] Preferably, the preparation method of the hydrophobic agent is: after mixing glycidyl methacrylate, diisopropylbenzene peroxide and polyethylene, adding them to a twin-screw extruder for melt extrusion to obtain the hydrophobic agent; the feed section temperature of the twin-screw extruder during the melt extrusion process is set to 160-190°C, the plasticizing section temperature is set to 190-210°C, the homogenizing section temperature is set to 200-220°C, and the screw speed is set to 100-300rpm.
[0024] It should be noted that the hydrophobic agent glycidyl methacrylate grafted polyethylene of the present invention can be homemade according to actual production requirements, or directly purchased from the market with the same performance requirements, as long as the same effect is achieved.
[0025] Preferably, the transesterification inhibitor is at least one of sodium dihydrogen phosphate, disodium dihydrogen pyrophosphate, and zinc monohydrogen phosphate.
[0026] Preferably, the toughening agent is at least one of ethylene-butyl acrylate-glycidyl methacrylate copolymer and ethylene-methyl acrylate-glycidyl methacrylate copolymer. Another object of the present invention is to provide a method for preparing the PC / PBT alloy material, comprising the following steps:
[0027] The components are mixed and then placed in a twin-screw extruder for melt extrusion and granulation to obtain the high-stability PC / PBT alloy material.
[0028] The preparation method of the high-stability PC / PBT alloy material of the present invention has simple operation steps, low requirements on production equipment, and can realize industrial-scale production.
[0029] Preferably, the feeding section temperature of the twin-screw extruder during the melt extrusion process is set to 180-220°C, the plasticizing section temperature is set to 220-240°C, the homogenizing section temperature is set to 240-260°C, and the screw speed is set to 300-600rpm.
[0030] Another object of the present invention is to provide application of the PC / PBT alloy material in the preparation of automotive parts.
[0031] As a preferred embodiment of the application of the present invention, the automobile parts include a grille, a rearview mirror housing, and a spoiler.
[0032] Another object of the present invention is to provide an automotive component, comprising the PC / PBT alloy material of the present invention or the PC / PBT alloy material prepared by the preparation method of the present invention.
[0033] Preferably, the automobile parts include a grille, a rearview mirror housing and a spoiler.
[0034] More preferably, the surface of the automobile part is provided with the glycidyl methacrylate grafted polypropylene.
[0035] The PC / PBT alloy material of the present invention has ideal mechanical properties after the combination of PC and PBT resins, and has good performance stability in the wet heat light aging environment. After 1000 hours of wet heat light aging environment testing, the highest impact performance and tensile strength retention rate of the obtained product can reach ≥90%, and the appearance color difference grayscale is ≥4 levels, with excellent comprehensive performance, and is very suitable for preparing automotive parts with high requirements for wet heat light aging performance. Especially for some automotive parts products without paint film on the surface, since the glycidyl methacrylate grafted polypropylene contained in the PC / PBT alloy material of the present invention has migration after the product is synthesized, it migrates from micro to macro to the surface of the component, and finally forms a macro glycidyl methacrylate grafted polypropylene protective layer on the surface of the component, which can replace the paint film to play a good protective, especially waterproof effect.
[0036] The beneficial effect of the present invention is that the present invention provides a PC / PBT alloy material, in which, in addition to introducing an ester exchange inhibitor, carbon nanotubes containing a specific content of carboxyl groups and a specific type of hydrophobic agent are introduced to work together, so that the final product has high comprehensive stability, especially in the face of a wet and hot light aging environment, it can have excellent mechanical properties and appearance performance stability without spraying an outer layer of protective paint. DETAILED DESCRIPTION
[0037] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments and comparative examples, the purpose of which is to understand the content of the present invention in detail, rather than to limit the present invention. All other embodiments obtained by those of ordinary skill in the art without making creative work premise belong to the protection scope of the present invention. The experimental reagents and instruments involved in the implementation of the present invention, unless otherwise specified, are all commonly used common reagents and instruments.
[0038] Examples 1 to 9
[0039] The PC / PBT alloy material and the preparation method thereof according to the present invention have components as shown in Table 1.
[0040] The preparation method of the PC / PBT alloy material comprises the following steps:
[0041] The components are mixed uniformly, and then placed in a twin-screw extruder for melt extrusion and granulation to obtain the high-stability PC / PBT alloy material;
[0042] In the process of melt extrusion, the temperature of the feeding section of the twin-screw extruder is set to 180-220° C., the temperature of the plasticizing section is set to 230-250° C., the temperature of the homogenizing section is set to 250-270° C., and the screw speed is set to 300-600 rpm.
[0043] Comparative Examples 1 to 11
[0044] The difference between the comparative examples and the embodiments is only in the types and proportions of components, as shown in Table 2.
[0045] Among the components described in each embodiment and comparative example,
[0046] PC resin 1 is FG1760 produced by Idemitsu of Japan, with a melt flow rate of 12 g / 10 min at 300 °C and a load of 1.2 kg;
[0047] PC resin 2 is FG1720 produced by Idemitsu of Japan, with a melt flow rate of 25 g / 10 min at 300 °C and a load of 1.2 kg;
[0048] PC resin 3 is PC 8001-10 produced by LG Chemical, with a melt flow rate of 10 g / 10 min at 300 °C and a load of 1.2 kg;
[0049] PBT resin 1 is GL236 produced by Sinopec Yizheng Chemical Fiber, with a melt flow rate of 5 g / 10 min at 250°C and a load of 1.2 kg;
[0050] PBT resin 2 is GX121 produced by Sinopec Yizheng Chemical Fiber, with a melt flow rate of 14 g / 10 min at 250°C and a load of 1.2 kg;
[0051] PBT resin 3 is GX122J produced by Sinopec Yizheng Chemical Fiber, with a melt flow rate of 8 g / 10 min at 250°C and a load of 1.2 kg;
[0052] The toughening agent is AX8700 produced by Arkema of France, ethylene-butyl acrylate-glycidyl methacrylate copolymer;
[0053] Transesterification inhibitor: commercially available sodium dihydrogen phosphate;
[0054] Hydrophobic agent 1: homemade glycidyl methacrylate grafted polyethylene, glycidyl methacrylate grafting rate is 0.6%;
[0055] The preparation method comprises the following steps: after uniformly mixing glycidyl methacrylate, polyethylene and dicumyl peroxide, placing the mixture in a twin-screw extruder for melt extrusion to obtain the hydrophobic agent; during the melt extrusion process, the feeding section temperature of the twin-screw extruder is set to 160-190° C., the plasticizing section temperature is set to 190-210° C., the homogenizing section temperature is set to 200-220° C., and the screw speed is set to 100-300 rpm, wherein the added mass ratio of glycidyl methacrylate, polyethylene and dicumyl peroxide is 2.5:97.5:0.2;
[0056] Hydrophobic agent 2: homemade glycidyl methacrylate grafted polyethylene, the glycidyl methacrylate grafting rate is 1.4%, the preparation method is the same as hydrophobic agent 1, wherein the added mass ratio of glycidyl methacrylate, polyethylene, and diisopropylbenzene peroxide is 2.5:97.5:0.6;
[0057] Hydrophobic agent 3: self-made glycidyl methacrylate grafted polyethylene, the grafting rate of glycidyl methacrylate is 0.3%, the preparation method is the same as hydrophobic agent 1, wherein the added mass ratio of glycidyl methacrylate, polyethylene, and diisopropylbenzene peroxide is 2.5:97.5:0.1;
[0058] Hydrophobic agent 4: self-made glycidyl methacrylate grafted polyethylene, the grafting rate of glycidyl methacrylate is 1.8%, the preparation method is the same as that of hydrophobic agent 1, wherein the added mass ratio of glycidyl methacrylate, polyethylene, and diisopropylbenzene peroxide is 2.5:97.5:0.8;
[0059] Hydrophobic agent 5: homemade glycidyl methacrylate grafted with acrylonitrile-butadiene-styrene, with a glycidyl methacrylate grafting rate of 0.6%;
[0060] The preparation method comprises the following steps: after glycidyl methacrylate, acrylonitrile-butadiene-styrene and dicumyl peroxide are uniformly mixed, the mixture is placed in a twin-screw extruder for melt extrusion to obtain the hydrophobic agent; during the melt extrusion process, the temperature of the feeding section of the twin-screw extruder is set to 170-190° C., the temperature of the plasticizing section is set to 190-210° C., the temperature of the homogenizing section is set to 200-220° C., and the screw speed is set to 100-300 rpm, wherein the mass ratio of glycidyl methacrylate, acrylonitrile-butadiene-styrene and dicumyl peroxide added is 2.5:97.5:0.3;
[0061] Carboxylated carbon nanotubes 1: carboxyl content 1.4wt%, homemade;
[0062] Carboxylated carbon nanotubes 2: carboxyl content 1wt%, homemade;
[0063] Carboxylated carbon nanotubes 3: carboxyl content 2wt%, homemade;
[0064] Carboxylated carbon nanotubes 4: carboxyl content 0.6wt%, homemade;
[0065] Carboxylated carbon nanotubes 5: carboxyl content 2.5wt%, homemade;
[0066] The preparation method of each carboxylated carbon nanotube is as follows: placing the carbon nanotube in a mixed acid (prepared by mixing concentrated sulfuric acid and nitric acid in a volume ratio of 3:1), ultrasonically treating for 2 to 5 hours and then refluxing at 80°C for 1 to 3 hours; then diluting with deionized water and leaving for 24 hours to precipitate until the supernatant is yellow; removing the supernatant, and filtering the lower dispersion with a polyvinylidene fluoride microfiltration membrane with a pore size of 0.2 μm and repeatedly washing with deionized water until the dispersion becomes neutral, and drying at 100°C to obtain the carboxylated carbon nanotube.
[0067] Hydroxylated carbon nanotubes: hydroxyl content of 1.85 wt%, brand TNGMH2, purchased from Chengdu Organic Chemistry Co., Ltd., Chinese Academy of Sciences;
[0068] Antioxidant: a mixture of commercially available hindered phenol antioxidant and commercially available phosphite antioxidant in a mass ratio of 1:2;
[0069] Ultraviolet light absorber: commercially available benzotriazole ultraviolet light absorber.
[0070] Unless otherwise specified, the components and raw materials used in the embodiments and comparative examples of the present invention are all commercially available raw materials, and the components and raw materials used in each parallel experiment are all of the same kind.
[0071] Table 1
[0072]
[0073] Table 2
[0074]
[0075]
[0076] In order to verify the performance of the PC / PBT alloy material of the present invention, the products prepared in each embodiment and comparative example were subjected to the following performance tests, and the specific steps are as follows:
[0077] (1) Tensile strength: According to DIN ISO 527-2-2003, each product was injection molded into a tensile specimen 5A specimen, and the tensile test speed was 50 mm / min;
[0078] (2) Impact strength: According to ISO 178-2019, each product was injection molded into an impact specimen with a size of 80×10×4 mm, and then cut into a specification of 10×15×4 mm and tested according to DIN 53453-1983.
[0079] (3) Appearance grayscale: tested according to DIN EN 20105-A02-1994;
[0080] (4) Wet heat light aging performance: According to MBN 10505-2014, the test is 102 minutes dry state and 18 minutes spraying. The humidity in the dry state is set to 60%, the temperature is set to 65°C, and the light intensity is set to 0.5W / m 2 (340nm), the treatment time is 1000h, and the tensile strength, impact strength and grayscale of the product are tested again according to the methods of steps (1) to (3) before and after the treatment, and the tensile strength retention rate, impact strength retention rate and appearance grayscale level are calculated respectively;
[0081] The test results are shown in Tables 3 and 4.
[0082] Table 3
[0083]
[0084]
[0085] Table 4
[0086]
[0087] It can be seen from Tables 3 and 4 that the tensile strength of the products in each embodiment can reach above 55Mpa, and the impact strength can reach 69KJ / m 2As above, after 1000h of wet heat light aging test, the retention rate of tensile strength and the retention rate of impact strength can reach more than 80%, and the gray level of appearance reaches more than 4, which basically meets the use requirements of automotive parts. From the comparison of the products obtained in Examples 5 to 8, it can be seen that on the basis of the product performance meeting the use requirements, when the carboxyl content of the carboxylated carbon nanotubes is preferably 1-2wt%, the comprehensive performance of the product is better, when the carboxyl content is lower, the tensile strength and performance retention rate of the product are slightly worse, and when the carboxyl content is higher, the impact strength and performance retention rate of the product are slightly worse. In contrast, the products of Comparative Examples 1 to 3 do not contain carboxylated carbon nanotubes and hydrophobic agents respectively or simultaneously, and the tensile strength and impact strength retention rate and grayscale performance of the products are obviously inferior to those of the embodiment products; in the products of Comparative Examples 4 and 5, since the melt flow rates of the two resins are not within the scope of the present invention, the two form a skin-core structure, and the products have poor resistance to wet heat and light aging; in the products of Comparative Examples 6 and 7, the grafting rate of glycidyl methacrylate of the hydrophobic agent is too high or too low, and the mechanical properties and resistance to wet heat and light aging of the products are affected; the product of Comparative Example 8 uses a non-preferred hydrophobic agent, and the product performance is still not ideal. The products of Comparative Examples 9 and 10 introduce too much hydrophobic agent and carboxylated carbon nanotubes during the preparation process, and the initial impact strength of the products is not good. At the same time, the appearance performance after the wet heat aging test is not as good as the embodiment products. From the performance results of the product of Comparative Example 11, it can be seen that although carbon nanotubes are also introduced as modified components, they are essentially hydroxylated carbon nanotubes, which are quite different from the effect of carboxylated carbon nanotubes defined in the scheme of the present invention.
[0088] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A PC / PBT alloy material, characterized in that: The composition comprises the following components in parts by weight: 55-75 parts of PC resin, 25-35 parts of PBT resin, 3-7 parts of toughening agent, 0.5-2 parts of carboxylated carbon nanotubes, 1-3 parts of hydrophobic agent and 0.2-0.5 parts of transesterification inhibitor; The ratio of the melt flow rate of the PC resin at 300° C. and 1.2 kg load to the melt flow rate of the PBT resin at 250° C. and 1.2 kg load is (1-3):1; The hydrophobic agent is glycidyl methacrylate grafted polyethylene, and the grafting rate is 0.5% to 1.5%.
2. The PC / PBT alloy material according to claim 1, characterized in that: The PC / PBT alloy material also includes 0.2 to 2 parts of processing aids.
3. The PC / PBT alloy material according to claim 2, characterized in that: The processing aid is at least one of an antioxidant and an ultraviolet absorber.
4. The PC / PBT alloy material according to claim 1, characterized in that: The carboxyl content of the carboxylated carbon nanotubes is 1-2 wt %.
5. The PC / PBT alloy material according to claim 1, characterized in that: The melt flow rate of the PC resin at 300° C. and a load of 1.2 kg is 8 to 15 g / 10 min; the melt flow rate of the PBT resin at 250° C. and a load of 1.2 kg is 5 to 8 g / 10 min.
6. The PC / PBT alloy material according to claim 1, characterized in that: The ester exchange inhibitor is at least one of sodium dihydrogen phosphate, disodium dihydrogen pyrophosphate, and zinc monohydrogen phosphate; the toughening agent is at least one of ethylene-butyl acrylate-glycidyl methacrylate copolymer and ethylene-methyl acrylate-glycidyl methacrylate copolymer.
7. The method for preparing the PC / PBT alloy material according to any one of claims 1 to 6, characterized in that: The following steps are involved: The components are mixed and then placed in a twin-screw extruder for melt extrusion and granulation to obtain the PC / PBT alloy material.
8. The method for preparing the PC / PBT alloy material according to claim 7, characterized in that: In the process of melt extrusion, the temperature of the feeding section of the twin-screw extruder is set to 180-220° C., the temperature of the plasticizing section is set to 220-240° C., the temperature of the homogenizing section is set to 240-260° C., and the screw speed is set to 300-600 rpm.
9. The method for preparing the PC / PBT alloy material according to claim 7, characterized in that: The preparation method of the hydrophobic agent in the components is as follows: after mixing glycidyl methacrylate, dicumyl peroxide and polyethylene, placing them in a twin-screw extruder for melt extrusion to obtain the hydrophobic agent; during the melt extrusion process, the feeding section temperature of the twin-screw extruder is set to 160-190° C., the plasticizing section temperature is set to 190-210° C., the homogenizing section temperature is set to 200-220° C., and the screw speed is set to 100-300 rpm.
10. Use of the PC / PBT alloy material according to any one of claims 1 to 6 in the preparation of automotive parts.
11. An automobile component, characterized in that: The invention comprises the PC / PBT alloy material according to any one of claims 1 to 6 or the PC / PBT alloy material prepared by the method according to any one of claims 7 to 9, wherein the automobile parts comprise a grille, a rearview mirror housing and a spoiler.
12. The automotive component according to claim 11, characterized in that: The glycidyl methacrylate grafted polyethylene is arranged on the surface of the automobile part.
Citation Information
Patent Citations
PC / PBT alloy and product thereof
CN108342056A
PC / ABS alloy with excellent damp-heat aging resistance and preparation method thereof
CN111234498A